The Mamluk Bridge at Dayr Sunayd - Blakely, Jeffrey A.; Czitron, Dror (Journal of Islamic Archaeology, 2020)
A long-overlooked Mamluk bridge spanning the Wadi al-Hasi (Nahal Shiqma) between Gaza and Majdal (Ashqelon) was built at the behest of Sultan Baybars about 1270, as mentioned by ’Izz al-Din Ibn Shaddad in his Ta’rikhal-Malik al-Zahir. It was also noted in a variety of travel accounts spanning the 17th through 19th centuries and it was even photographed in the 1880s. Later it became a point of interest during the Great War when it was shelled by the British Navy as part of the Third Battle of Gaza, yet it survived to be repaired. Since it was on an important road even in 1948, it was destroyed by a unit of Palmach in an attempt to impact infrastructure. The bridge is one of the smallest of the six known Baybars bridges, yet it fully fits with the technological characteristics of the other examples.